Spatial justice in healthcare: Advancing equitable geographic access to primary healthcare in Migori County, Kenya - Antony Ondiwa Okundi; Cigdem Varol (Social Sciences and Humanities Open, 2024)
This study aims to demonstrate the utility of location-allocation models in promoting spatial justice and enhancing access to primary healthcare services. Given the limitations of healthcare resources, it is essential to develop sustainable and equitable frameworks for primary healthcare. To accomplish this, the study utilizes the Maximum Covering Location Problem (MCLP) to assess the existing level of access in Migori County and to propose a viable approach for improving access. The proposed approach achieved a spatial coverage rate of 96%, a notable improvement compared to the existing rate of 84%. Therefore, the planning intervention serves as a viable spatial framework to complement the implementation of the Kenya Primary Health Care Strategic Framework (2019–2024) within the county. The study concludes by emphasizing the importance of policymakers and healthcare providers prioritizing the elimination of geographical disparities in primary healthcare access to foster spatial justice and an efficient referral system.